Patient monitoring across the spectrum of heart failure disease management 10 years after the CHAMPION trial. (13th August 2021) - Abraham, William T.; Bensimhon, Daniel; Pinney, Sean P.; Feitell, Scott C.; Peacock, W. Frank; Amir, Offer; Burkhoff, Daniel
Abstract: Despite significant advances in drug‐based and device‐based therapies, heart failure remains a major and growing public health problem associated with substantial disability, frequent hospitalizations, and high economic costs. Keeping patients well and out of the hospital has become a major focus of heart failure disease management. Achieving and maintaining such stability in heart failure patients requires a holistic approach, which includes at least the management of the underlying heart disease, the management of comorbidities and the social and psychological aspects of the disease, and the management of haemodynamic/fluid status. In this regard, accurate assessment of elevated ventricular filling pressures or volume overload, that is, haemodynamic or pulmonary congestion, respectively, before the onset of worsening heart failure symptoms represents an important management strategy. Unfortunately, conventional methods for assessing congestion, such as physical examination and monitoring of symptoms and daily weights, are insensitive markers of worsening heart failure. Assessment tools that directly measure congestion, accurately and in absolute terms, provide more actionable information that enables the application of treatment algorithms designed to restore patient stability, in a variety of clinical settings. Two such assessment tools, implantable haemodynamic monitors and remote dielectric sensing (ReDS), meet the prerequisites for useful heart failure management tools, by providing accurate, absolute, and actionable measures of congestion, to guide patient management. This review focuses on the use of such technologies, across the spectrum of heart failure treatment settings. Clinical data are presented that support the broad use of pulmonary artery pressure‐guided and/or ReDS‐guided heart failure management in heart failure patients with reduced and preserved left ventricular ejection fraction.